Peculiarities of the competitive specialists training in agricultural higher education institutions: social and humanitarian dimensions - Prokopova, O.; Liaska, O.; Верхоланцева, Валентина Олександрівна; Верхоланцева, Валентина Александровна; Verkholantseva, Valentyna (My University, 2018)
Human sciences take pride of place in higher vocational education. This article provides a short discussion of the importance of some humanities for both a person educated in a certain professional institution and for the educational system in general. Philosophy, political studies, sociology, and history are among such crucial disciplines.
Keywords: the humanities (human sciences); higher education; vocational education; trade education; education; educator; political studies; sociology; philosophy